PELAKSANAAN PENGADAAN BARANG/JASA SECARA ELEKTRONIK (E-PROCUREMENT) PADA PEMERINTAH KOTA YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Yogyakarta municipality is committed to improve the quality of its procurement procedures by applying electronic procurement system, which finds its standing on Mayor Regulation Nr. 13 of /2009. Two issues are going to be addressed: first, whether the purpose of e-procurement has been served and second, what are the obstacles that occur in its implementation.